Pendidikan Kesehatan tentang Perilaku Kekerasan terhadap Peningkatan Pengetahuan Keluarga Penderita Skozofrenia - Rahmi Dwi Yanti (Prosiding Seminar Kesehatan Nasional, 2022)
Violent behavior is a form of behavior that aims to injure someone physically or psychologically. Violent behavior can be done verbally, directed at oneself, others, and the environment. Violent behavior towards others is an aggressive act intended to injure or kill another person. Violent behavior in the environment can be in the form of behavior that destroys the environment, throwing glass, tiles and everything in the environment.The number of Schizophrenic Patients and diagnosed with Violent Behavior, Based on Nursing Diagnosis in the Inpatient Room of the Jambi Regional Mental Hospital in 2018 was 98 people and continues to increase until now. Efforts used to control violent behavior include medical management such as pharmacology, modality therapy, family therapy, and group therapy. A very important family action is that after the client returns home, the family accompanies the client for follow-up care at the nearest health center or hospital, for example in the first month: 2 times per month, second month: 2 times 7 per month, third month: 2 times per month and then 1 time per month. The activities of the service carried out were providing socialization about Violent Behavior towards Increasing Knowledge of Families of Schizophrenia Patients. The activity was carried out on 10 families who visited the outpatient polyclinic of the Jambi Province Mental Hospital. Families are able to participate in socialization activities well. The results obtained were an increase in the knowledge of the patient's family about violent behavior.